Financing for tuberculosis prevention, diagnosis and treatment services in the Western Pacific Region in 2005–2020 - Morishita, Fukushi; Elsayed, Hend; Islam, Tauhid; Rahevar, Kalpeshsinh; Oh, Kyung Hyun; Yanagawa, Manami; Floyd, Katherine; Garcia Baena, Inés (Western Pacific Surveillance and Response, 2023)
Objective: This paper provides an overview of financing for tuberculosis (TB) prevention, diagnostic and treatment services in the World Health Organization (WHO) Western Pacific Region during 2005–2020.Methods: This analysis uses the WHO global TB finance database to describe TB funding during 2005–2020 in 18 low- and middle-income countries (LMICs) in the Western Pacific Region, with additional country-level data and analysis for seven priority countries: Cambodia, China, the Lao People’s Democratic Republic, Mongolia, Papua New Guinea, the Philippines and Viet Nam.Results: Funding for the provision of TB prevention, diagnostic and treatment services in the 18 LMICs tripled from US$ 358 million in 2005 to US$ 1061 million in 2020, driven largely by increases in domestic funding, which rose from US$ 325 million to US$ 939 million over the same period. In the seven priority countries, TB investments also tripled, from US$ 340 million in 2005 to US$ 1020 million in 2020. China alone accounted for much of this growth, increasing its financing for TB programmes and services five-fold, from US$ 160 million to US$ 784 million. The latest country forecasts estimate that US$ 3.8 billion will be required to fight TB in the seven priority countries by 2025, which means that unless additional funding is mobilized, the funding gap will increase from US$ 326 million in 2020 to US$ 830 million by 2025.Discussion: Increases in domestic funding over the past 15 years reflect a firm political commitment to ending TB. However, current funding levels do not meet the required needs to finance the national TB strategic plans in the priority countries. An urgent step-up of public financing efforts is required to reduce the burden of TB in the Western Pacific Region.
Keywords: tuberculosis; health financing; preventive medicine; diagnosis; treatment; Asia